Modifikasi Kapasitas Belt Conveyor dari Kapasitas 400 Ton/Jam Menjadi 600 Ton/jam di Indarung IV PT. Semen Padang - Fanani; Rahmadhani; Mulyadi; Aidil Zamri; Yuli Yetri (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
Belt conveyor is a means of transportation used at Indarung IV PT. Semen Padang. Belt conveyor functions to move material from one place to another both in short distances and long distances with a certain slope. The capacity of limestone conveyor belt owned by Indarung IV is 400 tons/hour. However, this capacity is no longer able to meet the needs of limestone as a raw material for making cement in Indarung IV which currently reaches a capacity of 600 tons/hour. For this reason, an analysis of the 400 ton/hour capacity conveyor belt is still capable of transporting the limestone material with a capacity of 600 tons/hour, using the CEMA (Conveyor Equipment Manufacturer Association) standard. From the calculation results obtained belt conveyor parameters for a capacity of 600 tons/hour such as maximum belt capacity, belt speed, as well as the motor power and gearbox power needed for a capacity of 600 tons/hour. Where, some of these parameters exceed the value of the parameters of the conveyor belt capacity of 400 tons/hour, so the 400 tons/hour conveyor belt is unable to carry a load of 600 tons/hour. Replacement of some components is needed so that a load of 600 tons/hour can be transported.